Role of Teachers in Elementary School - Subhash Mahadeo Shekokar (AG Volumes, 2022)
Since the first edition of the Encyclopedia of Education was published, there has been a considerable shift in the roles and duties that elementary and secondary school teachers are expected to fulfil in their classrooms. Throughout history, educators have been seen as those who disseminate subject matter expertise and academic abilities. However, in the early twenty-first century, educators have expanded their roles to include serving as ambassadors to multicultural communities and as propagandists for democracy. The phrase "teaching profession" has grown more widespread as a direct result of the elevated standards of performance that have been placed on educators. Many educators are at the vanguard of this movement because they are rethinking all element of their occupations, including their connections with students, colleagues and the community; their techniques and tools; their rights and duties; the structure and substance of curriculum; what standards to establish and how to assess whether or not they are being fulfilled; their training as educators and continuous professional development; as well as the very architettura of the school. In a nutshell, educators are rethinking not just their profession but also their roles within it in order to better serve students and schools.